Taking a united stand on funding. (2nd August 2019) - Leitch, Neil
Abstract : The Alliance's Action Week demonstrated the sector's commitment to fairer funding and passion for its vital work. Providers are a 'force to be reckoned with' and the Government will ignore them at its peril.